Hypofractionated radiation therapy (HFRT) versus conventional fractionated radiation therapy (CRT) for newly diagnosed glioblastoma patients. A propensity score matched analysis. Issue 1 (April 2018) - Navarria, Pierina; Pessina, Federico; Franzese, Ciro; Tomatis, Stefano; Perrino, Matteo; Cozzi, Luca; Simonelli, Matteo; Bello, Lorenzo; Clerici, Elena; Riva, Marco; Santoro, Armando; Scorsetti, Marta
Abstract: Background: The current treatment for newly diagnosed glioblastoma consists of surgery followed by conventional radiotherapy (CRT) with concomitant and adjuvant chemotherapy. Hypofractionated radiation therapy (HFRT) has been investigated and it resulted feasible and safe. The aim of this study was to evaluate whether HFRT can be comparable to CRT. Materials and methods: The analysis included newly diagnosed glioblastoma patients treated with CRT 60 Gy/30 fractions or HFRT 60 Gy/15 fractions. A propensity score matching analysis (PSM) was performed using a logistic regression that considered age, KPS, extent of surgery, MGMT and IDH status. Results: A total of 267 patients were included; before PSM 169 were in CRT-group and 98 in HRFT-group. After 1:1 matching, 82 patients resulted in each group. The median OS time was 17.9 months for the CRT-group and 16.7 months for the HFRT-group; the 1, 2, 3-year OS rates were 75.6%, 32.7%, and 15.5% for the CRT-group, and 75.6%, 33.3%, and 18.9% for the HFRT-group ( p value = 0.8). No statistically significant differences were recorded between the two radiation therapy treatments performed. Conclusions: A short course of radiation therapy would seem comparable to CRT in terms of outcome and less burdensome for these poor prognosis patients.